2020
DOI: 10.1002/onco.13583
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Clinical Trial of Pembrolizumab and Enobosarm in Patients with Androgen Receptor-Positive Metastatic Triple-Negative Breast Cancer

Abstract: Lessons Learned The combination of enobosarm and pembrolizumab was well tolerated and showed a modest clinical benefit rate of 25% at 16 weeks. Future trials investigating androgen receptor‐targeted therapy in combination with immune checkpoint inhibitors are warranted. Background Luminal androgen receptor is a distinct molecular subtype of triple‐negative breast cancer (TNBC) defined by overexpression of androgen receptor (AR). AR‐targeted therapy has shown modest activity in AR‐positive (AR+) TNBC. Enobosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 66 publications
2
30
0
1
Order By: Relevance
“…However, not all combinations of drugs and checkpoint inhibitors were proved to be successful. Although the co-administration of pembrolizumab and enobosarm, a selective androgen receptor modulator, in the androgen receptor-positive subtype of TNBC, showed only a modest antitumor response [ 92 ], it still warrants further studies exploring the use of the checkpoint inhibitors. Moreover, to increase the expression of the target checkpoints, a broad range of drugs is constantly investigated, including the classical ones.…”
Section: Immunotherapeutic Strategies In Breast Cancermentioning
confidence: 99%
“…However, not all combinations of drugs and checkpoint inhibitors were proved to be successful. Although the co-administration of pembrolizumab and enobosarm, a selective androgen receptor modulator, in the androgen receptor-positive subtype of TNBC, showed only a modest antitumor response [ 92 ], it still warrants further studies exploring the use of the checkpoint inhibitors. Moreover, to increase the expression of the target checkpoints, a broad range of drugs is constantly investigated, including the classical ones.…”
Section: Immunotherapeutic Strategies In Breast Cancermentioning
confidence: 99%
“…GTX-024 and a related SARM, GTX-027, suppressed the growth of triple-negative breast cancer (TNBC) xenografts without adverse effects on animal health (34). GTX-024 has been evaluated in phase II clinical trials of AR-positive breast cancer (NCT02971761; NCT02368691), with no reported adverse safety signals (35). SARM-2F was shown to support muscle, prostate, and seminal vesicle mass in rats following castration and improved outcomes in a model of cancer cachexia (23).…”
Section: Sarms and Androgens Repress The Growth Of Pc Cells And Induce Concordant Transcriptional Changesmentioning
confidence: 99%
“…In a phase I/II study, metastasized patients with a positive androgen receptor status at mRNA level benefited from anti-androgen receptor-hormonal therapy, so that may be an option to bypass chemoresistance and to de-escalate chemotherapy [36]. Considering the unfavorable prognosis of patients with LAR subtype, a combination of immune checkpoint inhibitors and androgen receptor-inhibiting treatment should also be studied [43].…”
Section: Discussionmentioning
confidence: 99%